Tendenzen der Stadtgeographischen Forschung in der Bundesrepublik Deutschland - Schöller, Peter (ERDKUNDE, 1973)
A review of the subjects covered by German-language publications in urban geography during the years 1952-70 reveals a number of major research themes. These include studies of individual cities, urban groups, urban types and the internal functional divisions of cities; research into the spatial organisation of central places; and the general theme of urban agglomerations and city regions. Since the war, the emphasis in urban geography has increasingly moved from monograph-type studies to problem-oriented work. The success of the social geography emphasis in problem formulation and research method has been the most important advance in analytical urban research over the last decades. As subject matter becomes more specialised, small area studies and case analyses with a quantitative basis are becoming more frequent. In this way research is becoming more important for urban development and town planning practice. There is, however, a noticeable lack, evident even in some very intensive studies, of general research criteria and principles of the kind which could integrate specific results into an overall comparative framework. In addition, it is plain that urban geography in Central Europe will never be able to do without qualitative and historic-genetic studies. Research into central places and their areas of influence has, over the last two decades, become a firmly integrated component of urban geography. The German 'Umland' methods, anchored broadly in knowledge of regional geography, have rendered valuable assistance to politicians and administrators in the process of local and regional government reform which has recently got under way. Precisely because of their empirical basis, central place studies have done more for the public image of geography than many abstract discussions about the basis of central place theory. In the future, investigations of central place behaviour in urban agglomerations, whose linkages are strongly influenced by socio-economic and age-specific circumstances, will be in the forefront of work in urban geography.